The Middle-Income Trap 2.0: The Increasing Role of Human Capital in the Age of Automation and Implications for Developing Asia - Linda Glawe; Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2020)
We modify the concept of the middle-income trap (MIT) against the background of the Fourth Industrial Revolution and the (future) challenges of automation (creating the concept of the "MIT 2.0") and discuss the implications for developing Asia. In particular, we analyze the impacts of automation, artificial intelligence, and digitalization on the growth drivers of emerging market economies and the MIT mechanism. Our findings suggest that improving human capital accumulation, particularly the upgrading of skills needed with the rapid advance of automation, will be key success factors for overcoming the MIT 2.0.
urn:nbn:de:hbz:708-dh9608
Keywords: J24; O10; O11; O15; O33; O47; O53; 330; automation; AI; human capital; middle-income trap; developing Asia; economic development; economic growth; employment